2011
DOI: 10.1002/jor.21439
|View full text |Cite
|
Sign up to set email alerts
|

Repair of rat cranial bone defects with nHAC/PLLA and BMP‐2‐related peptide or rhBMP‐2

Abstract: An ideal artificial substitute has good biocompatibility properties and is able to provide for rapid bone formation. Bone morphogenetic protein-2 (BMP-2) is considered as one of the most important growth factors for bone regeneration. In this study, a synthetic BMP-2-related peptide (designated P24) corresponding to residues of the knuckle epitope of BMP-2 was introduced into a bioactive scaffold based on nano-hydroxyapatite/collagen/poly(L-lactic acid) (nHAC/PLLA); its in vitro release kinetics was then measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
93
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 45 publications
1
93
0
4
Order By: Relevance
“…Li et al measured osteoinductivity of the BMP-2 peptide loaded in nano-hydroxy apatite/collagen/ poly(l-lactic acid) scaffolds by implantation in a rat calvarial defect. 55 They reported that 3 mg of the BMP-2 peptide loaded in the scaffold had osteoinductive potential similar to 1 mg of BMP-2 protein, indicating that 3000-fold higher BMP-2 peptide concentrations were required to achieve the same activity as the protein. Our results demonstrate that although the addition of the BMP-2 peptide significantly increased osteoinductive potential, the level of activity was much less than that of BMP-2 protein even at 12,000-fold higher molar concentrations (1000-fold higher mass concentrations).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al measured osteoinductivity of the BMP-2 peptide loaded in nano-hydroxy apatite/collagen/ poly(l-lactic acid) scaffolds by implantation in a rat calvarial defect. 55 They reported that 3 mg of the BMP-2 peptide loaded in the scaffold had osteoinductive potential similar to 1 mg of BMP-2 protein, indicating that 3000-fold higher BMP-2 peptide concentrations were required to achieve the same activity as the protein. Our results demonstrate that although the addition of the BMP-2 peptide significantly increased osteoinductive potential, the level of activity was much less than that of BMP-2 protein even at 12,000-fold higher molar concentrations (1000-fold higher mass concentrations).…”
Section: Discussionmentioning
confidence: 99%
“…Combination of poly L-lactic acid nanofiber scaffold with omentum graft for bone healing in experimental defect in tibia of rabbits conductivity properties and also induced osteoinduction 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Various methods for bone defect treatments have been developed using biological or synthetic grafts (Chen et al, 2011;Huang et al, 2011;Li et al, 2011). In clinic, the gold standard of grafting material used in bone repairs is autologous bone.…”
Section: Introductionmentioning
confidence: 99%